Perancangan Konsep Media Pembelajaran Berbasis Board Game untuk mengenalkan “4 Sifat Wajib Rasul” dalam Pelajaran Akidah dan Akhlak - Sukma Ayu Susilowati; Pungky Febi Arifianto; Bayu Setiawan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This research aims to design and develop an educational board game titled "The 4 Obligatory Attributes of the Prophets" as an engaging and effective learning medium for Islamic Creed (Aqidah) and Morals (Akhlak) to enhance the understanding of elementary school students aged 9–10 years. The background of this research is the necessity for innovative and interactive learning media to instill the fundamental concepts of Aqidah and Akhlak, particularly regarding the four obligatory attributes of Prophet Muhammad SAW, in students. The research method employed is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The board game design process includes analyzing the needs of students and teachers, designing fun and educational game mechanics, developing game components (board, cards, pawns, and rules), validation by material experts and media experts, and limited trials with target students. The research is expected to produce a valid, practical, and effective board game in improving students' understanding of the four obligatory attributes of the Prophets (Siddiq, Amanah, Tabligh, and Fathonah), thus providing an attractive alternative learning medium for elementary school teachers.